First report of 'mining' as a feeding behaviour among Australian manna‐feeding birds. (10th March 2016) - Case, Samuel B.; Edworthy, Amanda B.
Abstract : The Forty‐spotted Pardalote Pardalotus quadragintus is an endangered songbird endemic to the forests of Tasmania, Australia. Forty‐spotted Pardalotes forage predominantly in the foliage of White (or Manna) Gums Eucalyptus viminalis for invertebrates, lerps (the protective coverings produced by psyllids) and manna, a crystallized exudate produced by certain Eucalyptus species. Although many Australian birds feed on manna, this study reports the first observations of birds actively stimulating manna production rather than feeding on it opportunistically. In light of these observations, we also compared rates of manna production across tree species and sizes, and quantified the relative importance of manna in nestling diet. Adult Forty‐spotted Pardalotes stimulated manna production by clipping leaf stalks with their bills, creating small incisions in the stem surface. We experimentally mimicked this behaviour and found that, in 53.7% of incisions of E. viminalis, manna flow was released within 3 days. However, none of the other three common tree species at our sites produced manna in response to the same experimental damage. There was no effect of tree size on manna production by E. viminalis . To determine the importance of manna and other food sources in nestling diet, we videotaped provisioning trips by adults to nests and surveyed food availability in E. viminalis foliage within territories. Manna was the most important food item, comprising 84.2% of identified food items provided to nestlings, and it was selected over 50 times more frequently than expected given its relative availability in the foliage. As a manna miner, the Forty‐spotted Pardalote is the first Australian bird to join the small number of bird species that mine sap or other exudates of trees. Their preference for manna as a food source, especially in nestling diet, provides an explanation for the species' specialization on E. viminalis, the only manna‐producing tree at our sites. Our results suggest that E. viminalis forests provide critical food supply for developing nestlings, and that restoration of E. viminalis forests will be critical to the long‐term viability of Forty‐spotted Pardalote populations.